Evaluation of IL8 pathway on the ocular surface: new insights in patients with ocular mucous membrane pemphigoid. Issue 2 (5th September 2019) - Bruscolini, Alice; Lambiase, Alessandro; Segatto, Marco; La Cava, Maurizio; Nebbioso, Marcella; Sacchetti, Marta
Abstract: Purpose: To evaluate the expression of IL8/CXCL8 cytokine and its receptor CXCR1 in tear film and ocular surface of patients with ocular mucous membrane pemphigoid (oMMP). Methods: Ten patients with oMMP in the quiescent phase, 20 patients with primary Sjogren syndrome (pSS) and 13 age‐ and sex‐matched healthy controls (HCs) were included in this study. All patients undergone complete eye examination including lacrimal function tests and ocular surface staining assessed by ocular staining score. Ocular mucous membrane pemphigoid (oMMP) staging according to Mondino classification and dry eye severity grade according to Dry Eye Workshop 2007 classification were recorded. Tear samples and conjunctival epithelium were collected. IL‐8 tear concentration was measured by enzyme‐linked immunosorbent assay, and conjunctival IL8 was analysed by Western blot; conjunctival expression of CXCR1 was evaluated by immunohistochemistry. Il‐8 and CXCR1 expression in oMMP patients were compared with HCand pSS patients and correlated with ocular clinical findings. Results: Tear levels of IL‐8 were significantly increased in patients with oMMP (260.1 ± 70 pg/ml) when compared to both HCs (98.5 ± 71.35 pg/ml; p = 0.001) and patients with pSS (96.3 ± 87.5 pg/ml; p = 0.001). Conjunctival expression of IL8 and CXCR1 was significantly increased in oMMP patients when compared to both healthy subjects and pSS patients. Conclusion: The significant increase of tear and conjunctival IL8 and CXCR1 levels in patients with oMMP when compared to healthy subjects and patients with Sjogren syndrome suggests that changes of IL8 pathway are specific of oMMP and may represent a potential biomarker of the disease and/or therapeutic target.